Comparing magnetopause predictions from two MHD models during a geomagnetic storm and a quiet period - Dredger, Pauline M.; Lopez, Ramon E.; Collado-Vega, Yaireska M. (Frontiers in Astronomy and Space Sciences, 2023)
Magnetopause location is an important prediction of numerical simulations of the magnetosphere, yet the models can err, either under-predicting or over-predicting the motion of the boundary.This study compares results from two of the most widely used magnetohydrodynamic (MHD) models, the Lyon-Fedder-Mobarry (LFM) model and the Space Weather Modeling Framework (SWMF), to data from the GOES 13 and 15 satellites during the geomagnetic storm on June 22, 2015, and to THEMIS A, D, and E during a quiet period on January 31, 2013. The models reproduce the magnetopause crossings of the spacecraft during the storm, but they also predict spurious magnetopause motion after the crossings seen in the GOES data. We investigate the possible causes of the over-predictions during the storm and find the following. First, using different ionospheric conductance models does not significantly alter predictions of magnetopause location. Second, coupling the Rice Convection Model (RCM) to the MHD codes improves the SWMF magnetopause predictions more than it does the LFM predictions. Third, SWMF produces a stronger ring current than LFM does, both with and without RCM and regardless of the LFM spatial resolution. During the non-storm event, LFM predicts the THEMIS magnetopause crossings due to southward interplanetary magnetic field better than the SWMF. Additionally, increasing the LFM spatial grid resolution improves the THEMIS predictions, while increasing the SWMF grid resolutions does not.